A rechargeable anti-thrombotic coating for blood-contacting devices. (September 2021) - Ham, Hyun Ok; Haller, Carolyn A.; Su, Guowei; Dai, Erbin; Patel, Madhukar S.; Liu, David R.; Liu, Jian; Chaikof, Elliot L.
Abstract: Despite the potential of anti-thrombogenic coatings, including heparinized surfaces, to improve the performance of blood-contacting devices, the inevitable deterioration of bioactivity remains an important factor in device failure and related thrombotic complications. As a consequence, the ability to restore the bioactivity of a surface coating after implantation of a blood-contacting device provides a potentially important strategy to enhance its clinical performance. Here, we report the regeneration of a multicomponent anti-thrombogenic coating through use of an evolved sortase A to mediate reversible transpeptidation. Both recombinant thrombomodulin and a chemoenzymatically synthesized ultra-low molecular weight heparin were repeatedly and selectively immobilized or removed in a sequential, alternating, or simultaneous manner. The generation of activated protein C (aPC) and inhibition of activated factor X (FXa) was consistent with the molecular composition of the surface. The fabrication of a rechargeable anti-thrombogenic surface was demonstrated on an expanded polytetrafluoroethylene (ePTFE) vascular graft with reconstitution of the surface bound coating 4 weeks after in vivo implantation in a rat model. Highlights: Rechargeable surface bound assembly of synthetic ultra-low molecular weight heparin. Rechargeable multicomponent thin film displaying anti-FXa and aPC generating activity. Rechargeable anti-thrombotic coating on an ePTFE graft after in vivo blood contact.